Symptom cluster of emotional distress, fatigue and cognitive difficulties among young and older breast cancer survivors: The mediating role of subjective stress. Issue 5 (September 2018) - Levkovich, Inbar; Cohen, Miri; Alon, Shirly; Kuchuk, Iryna; Nissenbaum, Bella; Evron, Ella; Pollack, Simon; Fried, Georgeta
Abstract: Objectives: To examine the nature of the symptom cluster of emotional distress, fatigue, and cognitive difficulties in young and older breast cancer survivors (BCS); To assess the mediating role of subjective stress and coping strategies (emotional control and meaning-focused coping) in the association between age and symptom cluster. Materials and Methods: Participants were 170 BCS, stages I-III, 1–12 months post-chemotherapy, filled-out the Fatigue, Emotional Control, Meaning—focused Coping, Emotional Distress and the Cognitive Difficulties Questionnaires. Statistical analyses included tests for difference between-groups Pearson correlations and Structural Equation Modeling for the assessment of the study model. Results: Older BCS (aged 60–82) reported lower levels of emotional distress (M = 0.87, SD = 0.87), fatigue (M = 3.85, SD = 2.38), and cognitive difficulties (M = 1.17, SD = 1.07) compared to the younger BCS (aged 24–59) (emotional distress M = 1.17, SD = 0.85, fatigue M = 5.02, SD = 2.32, and cognitive difficulties M = 1.66, SD = 1.23, p < .01–, 05). The older survivors reported lower levels of subjective stress and used more emotional control strategies compared to the younger BCS. The empirical model had good fit indices ( χ 2 = 27.60, p = 0.20, χ 2/df = 1.26; CFI = 0.98; TLI = 0.98; NFI = 0.95; RMSEA = 0.04 (90% CI = 0.00, 10) and showed that subjective stress, but not coping strategies, mediated the effect of age on symptom cluster severity. Conclusions: Lower levels of subjective stress, but not coping strategies, mediated the association of age with the symptom cluster of emotional distress, fatigue and cognitive difficulties. Further research is needed to explore differences in subjective stress by age.